PENGARUH REMUNERASI, KOMPENSASI NON FINANSIAL, DAN GAYA KEPEMIMPINAN DEMOKRATIS TERHADAP MOTIVASI KERJA - Annisa Miftah Nuzulla (JURNAL EKOBIS DEWANTARA, 2019)
The purpose of this study was to determine the effect of remuneration, non-financial compensation, the democratic leadership style towards employee work motivation at PT Taspen (Persero), Branch of Yogyakarta. This study began with collecting data through questionnaire method by taking a sample of the entire population of 35. Data analysis which was used including validity test, reliability test, classic assumption test (normality test, multicollinearity test, heterocedasticity test), simple linear regression test, and multiple linear regression test. The results showed that.there was a positive effect of remuneration, non-financial compensation, and the democratic leadership style simultaneously towards employee work motivation shown by Fcount >Ftable (19,513>2,91) in signification value of 5% and regression coefficients in positive value of 0,809 (sig. 0,000>0,05). Employee work motivation were influenced by remuneration, non-financial compensation, the democratic leadership style of 62% and the rest 38% were influenced by other variable which was not researched.